Multas por exceso de velocidad en el cantón Ambato y el principio de Proporcionalidad - García Taipe, Shirley Nicole (2024)
ABSTRACT: The sanctions or fines in traffic violations due to speeding in the Ambato canton and the principle of proportionality, it will be very useful to carry out a doctrinal foundation of the different types of penalties, in which to base the application of these in said infractions, regarding speeding. Followed by it, it starts from the definition and conceptualization of the types of traffic violations in accordance with the norm, to later arrive at the construction of an analysis of the application of penalties, through which, it starts from theoretical background and legal, have been analyzed throughout history. Likewise, the use of this principle has as an important objective to avoid committing some type of outrage or abuse and in the same way the disproportion in the materialization of a sentence, it must take into consideration, since both the crime committed and the personality of the offender must be analyzed within a real dimension. Finally, the general objective of this investigation was to analyze whether or not there is a violation of the principle of proportionality in fines for speeding in the Ambato canton, in order to establish whether the Ecuadorian state guarantees said principle. By virtue of that, a review of various sources has been carried out; the level of research is descriptive, document and field helps us determine how big the problem is and how it affects society; the research design with which the inquiry was carried out is non-experimental; Regarding the research instrument, it was carried out through surveys which were directed to the people who have been involved in this ill-being that affects the citizens of Ambato, in this way we have been able to obtain the necessary information to solve the problem posed.